Leadership Practices of Effective Rural Superintendents: Connections to Waters and Marzano's Leadership Correlates - Mark Forner; Louann Bierlein-Palmer; Patricia Reeves (Journal of Research in Rural Education, 2012)
This study examined the leadership practices of seven rural superintendents, selected via a sampling strategy which identified disadvantaged rural districts that had experienced marked increased in test scores during the superintendent's tenure. Researchers examined how the practices of these superintendents were linked to Waters and Marzano's (2006) six correlates of effective leadership practices (which had not necessarily been developed using data from rural districts). A multi-case study approach was utilized involving a site visit to each of seven rural districts, including interviews with four individuals: the superintendent, one principal, one teacher, and one board trustee. Secondary sources included a review of board meeting minutes, school newsletters, school memoranda, and observations. Findings revealed seven core leadership practices, consistent with previous research on leadership, with one exception. The goal-setting in these rural districts was largely driven by the superintendent, not necessarily a formal, collaborative bottom-up process. Other effective leadership practices for these rural superintendents involved building support for reform through direct, personal conversations; using constructive confrontations to assist struggling students and teachers; removing low-performing teachers and principals; leveraging close working relations with building principals; taking a hard line in union contract negotiations; and realigning financial commitments to match district priorities focused on student outcomes.